Correlation between Macronutrient Intake and Body Weight among Adults and Elderly Prolanis Participants - Andi Eka Yunianto; Sutrio Sutrio; Sefanadia Putri (Media Publikasi Cendekia Indonesia, 2026)
Prolanis is a chronic disease management program for seniors where the focus is on promoting and preventing chronic disease; however, currently limited research has examined the correlation between nutritional intake and body weight within elderly Prolanis participants. The objective of this study was to investigate the relationship between specific macronutrient intake therefore measuring energy, protein, fat, carbohydrates, and fibre and body weight for older Prolanis participants. This study employed a cross-sectional research design consisting of 42 elderly Prolanis participants from the Kedaton Public Health Centre in Bandar Lampung. Nutritional intake data were recorded using 2x24-hour food recall and analysed through a nutrition analysis program. Body weight was measured using a calibrated digital scale. Data from this study were evaluated using Pearson rank correlations and multiple linear regression analyses. Statistically significant associations were found between each type of macronutrient (energy - p=0.034; r=0.328), protein - p=0.011, r=0.391), fat - p<0.001, r=0.578), and fibre - p=0.002; r=0.472) and body weight. Of all the different types of macronutrients, fat intake was statistically the most important predictor of body weight in older adults (p=0.008). There was no statistically significant correlation between carbohydrate intake and body weight (p=0.212). Thus, among Prolanis participants, the intake of all types of macronutrients - in particular, fat intake - has statistically significant associations with body weight. Therefore, the Prolanis program has an opportunity to strengthen nutrition-based education and dietary monitoring to ensure that older adults maintain optimal nutritional status.